Struktur Gerak Tari Mulo Pado Di Kanagarian Padang Magek Kecamatan Rambatan Kabupaten Tanah Datar Sumatera Barat (SENDRATASIK UNP, 2022)
This article aims to describe and analyze the structure of the Mulo Pado Dance, in KaNagarian Padang Magek. This research is a qualitative research, the object of research is the Mulo Pado Dance in Kanagarian Padang Magek. Data were collected through literature study, observation, interviews, and documentation, assisted by supporting instruments such as stationery, and photo and video cameras, as well as audio-visual equipment. The data were analyzed in the following stages, namely collecting data, reducing data or selecting data, presenting data, and testing data and concluding the results of the analysis. The results of the study are that the basic elements of the Mulo Pado Dance movement have basic elements related to attitude and movement, starting from the head, body, hands and feet. From the relationship between the basic elements, it produces motifs. There are 55 motifs, 19 phrases, 9 motion sentences, and 1 cluster in the hierarchical relationship of the Mulo Pado dance. It was found that there was a syntagmatic relationship in the structure of the Mulo Pado dance movement. Syntagmatic relations can be interpreted as a system of relationships such as links, which cannot be separated or exchanged between one another.